Electrocatalytic Reduction of Hydrogen Peroxide on Palladium-Gold Codeposits on Glassy Carbon: Applications to the Design of Interference-Free Glucose Biosensor - Elena Horozova; Totka Dodevska; Nina Dimcheva; Ruska Mussarlieva (International Journal of Electrochemistry)
Following our previous studies on the catalytic activity electrochemically codeposited on graphite Pd-Pt electrocatalysts for hydrogen peroxide electroreduction, a series of glassy carbon electrodes were modified with Pd or (Pd+Au) deposits aiming at the development of even more efficient electrocatalysts for the same process. The resulting electrodes were found to be very effective at low applied potentials (−100 and −50 mV versus Ag/AgCl, 1 M KCl). The surface topography of the electrode modified with Pd+Au mixed in proportions 90% : 10%, exhibiting optimal combination of sensitivity and linear dynamic range towards hydrogen peroxide electrochemical reduction, was studied with SEM and AFM. The applicability of the same electrode as transducer in an amperometric biosensor for glucose assay was demonstrated. At an applied potential of −50 mV, the following were determined: detection limit (S/N=3) of 6×10−6 M glucose, electrode sensitivity of 0.15 μA μM−1, and strict linearity up to concentration of 3×10−4 M.